Factors Influencing Perceived CPR Hands-Only Skill Retention Among High School Students - Rantung, Gilny Aileen Joan; Aregay, Atsede Fantahun (Jurnal Kesehatan Manarang, 2024)
Retention refers to an individual's ability to retain or recall information, knowledge, or skills acquired through learning. Proficiency in performing Cardiopulmonary Resuscitation (CPR) is essential for high school students to enhance their preparedness for emergencies. One of the most straightforward CPR techniques for laypersons is CPR Hands-Only. This study aims to identify the factors influencing the post-training self-assessed perceived retention of CPR skills among high school students. A cross-sectional approach was employed, involving 111 high school students participating in a CPR Hands-Only training program. Participants were selected using a purposive sampling technique. Data were collected using structured self-assessment questionnaires to evaluate age, gender, class level, history of witnessing heart attacks, prior CPR training, knowledge, confidence, and perceived skill retention. Multivariate logistic regression was used for data analysis. Class level, knowledge, and confidence are found to influence CPR skill retention (p<0.05) significantly. 76.6% of participants have reported perceiving themselves as capable of retaining CPR skills, with most demonstrating moderate to high levels of knowledge and confidence. Age and gender do not have a significant impact, and prior exposure to heart attacks or CPR training also shows no notable effect on skill retention. The findings indicate that educational level, knowledge enhancement, and confidence-building are critical factors for successful CPR skill retention. Adapting training methods to these factors can improve training effectiveness and emergency preparedness, particularly in regions like Indonesia, where CPR training is not yet routinely integrated into school programs.